1998
DOI: 10.1042/bj3290313
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of diadenosine 5′,5‴-P1,P4-tetraphosphate hydrolase from Lupinus angustifolius L

Abstract: The first isolation, cloning and expression of cDNA encoding an asymmetric diadenosine 5',5'''P1,P4-tetraphosphate pyrophosphohydrolase (Ap4A hydrolase) from a higher plant is described. Ap4A hydrolase protein was purified from seeds of both Lupinus luteus and Lupinus angustifolius and partially sequenced. The Ap4A hydrolase cDNA was cloned from L. angustifolius cotyledonary polyadenylated RNA using reverse transcription and PCR with primers based on the amino acid sequence. The cDNA encoded a protein of 199 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
(63 reference statements)
2
36
0
2
Order By: Relevance
“…DIPP represents the first hydrolase in the animal kingdom shown to prefer Ap 6 A and Ap 5 A over Ap 4 A. In fact, the kinetic parameters associated with DIPP-dependent Ap 6 A/Ap 5 A hydrolase activity are not only similar to those of Aps1 and YOR163w (Tables I and II), they are also in line with the characteristics of other MutT motif Ap n A hydrolases (25)(26)(27)(28)30). In that sense, DIPP is a typical Ap 6 A/Ap 5 A hydrolase.…”
Section: Discussionsupporting
confidence: 68%
“…DIPP represents the first hydrolase in the animal kingdom shown to prefer Ap 6 A and Ap 5 A over Ap 4 A. In fact, the kinetic parameters associated with DIPP-dependent Ap 6 A/Ap 5 A hydrolase activity are not only similar to those of Aps1 and YOR163w (Tables I and II), they are also in line with the characteristics of other MutT motif Ap n A hydrolases (25)(26)(27)(28)30). In that sense, DIPP is a typical Ap 6 A/Ap 5 A hydrolase.…”
Section: Discussionsupporting
confidence: 68%
“…The sequences corresponding to the mature chloroplastic AtNUDX26 showed 57.7% homology with that of AtNUDX27. Both AtNUDX26 and AtNUDX27 shared high similarity (69.8% and 59.2%, respectively) to a Nudix hydrolase that acts on asymmetric diadenosine tetraphosphates (Ap 4 A) from Lupinus angustifolius (Maksel et al, 1998). The deduced amino acid sequences of other predicted organelle-type AtNUDXs showed no significant homology to any conserved motifs, except the Nudix motif, in Nudix hydrolases from various organisms.…”
Section: Organelle-type Nudix Hydrolases In Arabidopsismentioning
confidence: 98%
“…Enzymological and structural studies have shown that this arrangement of amino acids leads to a novel loop-helix-loop motif involved in substrate binding and catalysis (2)(3)(4)(5)(6)(7)(8). A recent BLAST (9) search of the data banks for the Nudix signature sequence has revealed over 800 open reading frames from more than 200 species including archaea, eubacteria, and eukarya, and at present, ϳ50 of the gene products have been identified.…”
mentioning
confidence: 99%